2015
DOI: 10.1007/s00464-015-4366-8
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of risk factors for pancreatic fistula after robotic pancreaticoduodenectomy: outcomes from a consecutive series of standardized pancreatic reconstructions

Abstract: Larger BMI, higher EBL, smaller tumor size and smaller duct diameter are the main predictors of POPF in RPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 41 publications
1
26
1
1
Order By: Relevance
“…In the robotic group, the POPF rate was lower than reported previously, and tended to be lower than for open surgery. Polanco et al . and Fu and colleagues both found that higher EBL and smaller pancreatic duct diameter were associated with a higher POPF rate, based on robotic and open pancreaticoduodenectomies.…”
Section: Discussionmentioning
confidence: 97%
“…In the robotic group, the POPF rate was lower than reported previously, and tended to be lower than for open surgery. Polanco et al . and Fu and colleagues both found that higher EBL and smaller pancreatic duct diameter were associated with a higher POPF rate, based on robotic and open pancreaticoduodenectomies.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have reported that risk factors for POPF included a higher BMI, soft pancreatic texture and a smaller pancreatic duct size . Several fistula risk scoring systems have been published , with one tested for its ability to predict POPF in a multicenter cohort .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even after controlling for confounding factors and bias, which are limitations of nonrandomized retrospective studies, PGA mesh could prevent clinically relevant POPF and its complications. Studies have reported that risk factors for POPF included a higher BMI, soft pancreatic texture and a smaller pancreatic duct size [31][32][33][34]. Several fistula risk scoring systems have been published [17,35], with one tested for its ability to predict POPF in a multicenter cohort [36].…”
Section: Discussionmentioning
confidence: 99%
“…Средняя продолжительность операции соста-вила 278±82,7 мин, интраоперационная кровопотеря -200±131,9 мл [14,23,24]. Послеоперационные осложнения возникли в 48% случаях, при этом панкреатический свищ составил 29,3% [23,[25][26][27]. Стандартный вариант техники РА-операций на ПЖ в настоящее время отсутствует.…”
Section: Discussionunclassified